Perception of Chemistry Teachers of the Transition to the Online Teaching Model, during the Global Emergency due to COVID-19 in 2020-2021 - Corrales González, Yorleni (2022)
This research analyzes the perspective of chemistry teachers regarding the transition into a 100% online teaching model, which was implemented as an adaptation to the emergency caused by COVID-19. Data collection was carried out through two surveys administered to 32 university teachers, the first one in May 2020, and the second one in January 2021, with the aim of contrasting the possible changes in perception after almost a year of experience in virtual teaching. Among the main results, it was found that teachers presented increased confidence in adapting their courses and using virtual technologies. In addition, teachers expressed a feeling of pedagogical dissatisfaction regarding the development of a virtual education modality and the possibility that students are not learning enough compared to face-to-face classes. However, it is recommended to take advantage of the opportunity for improvement in teacher training that has been generated by the methodological change in teaching.